2020
DOI: 10.3390/cells9071634
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Inhibitor with Selectivity for Trimeric MMP-9 Amplifies Neutrophil Chemotaxis and Enables Functional Studies on MMP-9 Proteoforms

Abstract: A fundamental part of the immune response to infection or injury is leukocyte migration. Matrix metalloproteinases (MMPs) are a class of secreted or cell-bound endopeptidases, implicated in every step of the process of inflammatory cell migration. Hence, specific inhibition of MMPs is an interesting approach to control inflammation. We evaluated the potential of a bivalent carboxylate inhibitor to selectively inhibit the trimeric proteoform of MMP-9 and compared this with a corresponding monovalent inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Recombinant human MMP-9 was produced, purified, activated and tested as described ( 27 ). Recombinant human proMMP-2, proMMP-7, proMMP-8 and ‘a disintegrin and metalloproteases’ (ADAM)17 were purchased from R&D Systems and activated as previously described ( 28 ). Active human NE was purchased from Abcam (cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant human MMP-9 was produced, purified, activated and tested as described ( 27 ). Recombinant human proMMP-2, proMMP-7, proMMP-8 and ‘a disintegrin and metalloproteases’ (ADAM)17 were purchased from R&D Systems and activated as previously described ( 28 ). Active human NE was purchased from Abcam (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil degranulates were collected from human blood granulocytes stimulated with N-formylmethionyl-leucyl-fenylalanine (fMLF), as previously described ( 21 , 28 ). All blood donors gave written informed consent in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…TIMP1 and PLAUR are involved in inflammation and hypoxia-related progression in ICH. MMP-9 is expressed in inflamed tissues and is involved in the inflammatory process ( 61 ). TIMP-1 is a natural inhibitor of MMP-9 ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, AKT1 phosphorylation could also be stimulated by lncRNA MALAT1 based on the recruitment of EZH2 and decrease of BRCA1 expression, thus accelerating inflammatory response to aggravating sepsis (9). Furthermore, in terms of MMP-9, it has been reported that the administration of inhibitors to inhibit the trimeric proteoform of MMP-9 selectively would increase the presence of neutrophils in the inflammation triggering site, suggesting a possible beneficial role of MMP-9 trimers in inhibiting excessive neutrophil migration or anti-inflammatory effect (10). Reckens et al found that MMP-9(-/-) mice developed more severe damage to distant organs during infection, implying that MMP-9 may be significantly involved in the effective host response to E. coli peritonitis (11).…”
Section: Roc Analysismentioning
confidence: 99%